THE FEMALE IN SELECTED LITERARY PIECES: A SOCIAL CRITICISM - Sourav Chandra Gorain,; Dr. Pralay Nayek, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
In the previous two decisive decades, feminism's enquirers have imprinted a vital rebuke to the way social science has etched out men, women, and society. Arguments regarding epistemology, method, and methodology have been entwined with confabulations about how to effectively modify skewed and partial accounts in the setting of traditional analyses from the dawn. To grasp the comprehensiveness of the social sciences' metamorphosis, to distinguish women and gender practices, one required to observe the most visible approaches to alter the classic analyses' andro-centrism. Feminists have attempted to 'include women' in these discussions. We find three types of women who emerged as undisputable candidates for this framework: women who contributed to public life and were already being studied by social scientists, women social scientists, and women who have been victims of the most abhorrent and blatant forms of male pre-eminence. This research article is an endeavor to study feminism taking selected literary pieces from Sanskrit, British English Literature and Indian English Literature.